Social Media Marketing pada Kopi Klotok Yogyakarta: Studi Empiris pada Instagram Kopi Klotok - Dhiya Shafa Nabila; Ratna Roostika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The objective of this research is to test and analyze the influence of social media marketing activities, brand awareness, brand image, electronic word of mouth, and commitment. Testing of the model and hypothesis was done with a sample of 225 respondents who were Yogyakarta klotok coffee consumers. Purposive sampling was the method of sampling that was applied. Partial Least Square (PLS) versi 3.0 was used to process the study hypothesis before the Structural Equation Modeling (SEM) approach was created to test it. Social media marketing initiatives, brand awareness, brand image, electronic word- of-mouth, and commitment are among the data variables employed in this instance. Six hypotheses are based on these variables. It is established from the study's findings that social media marketing initiatives improve brand recognition and perception. Positive brand awareness and image impact electronic word-of-mouth. Brand recognition and image positively impact commitment